Effects of diuron and 3,4-dichloroaniline on reproduction and early development of Javanese medaka (Oryzias javanicus, Bleeker 1854) - Adamu, Ibrahim Musa (2021)
The indiscriminate application of pesticides in the environment affects human and wildlife health worldwide. Diuron, a chlorinated phenylurea herbicide and its primary metabolite, 3,4-dichloroaniline (3,4-DCA) exert toxic effects on non-target organisms. Growth, survival, and reproduction are the primary factors determining an organism's population structure in its habitat. Javanese medaka (Oryzias javanicus) is an emerging euryhaline model fish distributed around the coastal and estuarine regions of Peninsular Malaysia and other parts of Southeast Asia. The fish is a sentinel species that bioindicates ecosystem health. The objectives of this study were to evaluate the acute toxicity of diuron and 3,4-DCA on different life stages of Javanese medaka, to determine the effect of diuron and 3,4-DCA on the fecundity and reproductive biomarkers of Javanese medaka, and to evaluate the embryotoxicity of diuron and 3,4-DCA on Javanese medaka. Larvae, juveniles, and adults of Javanese medaka were exposed to diuron and 3,4-DCA for 96 hours to determine mortality (96 hour-LC50; 50% lethal concentration to exposed organisms) and behavioural toxicity symptoms. Fish embryo toxicity (FET) test; mortality (LC50) at 10-days and 96-hour for diuron and 3,4-DCA, and subchronic embryonic toxicity (20 days) for both diuron and 3,4-DCA were also evaluated. Reproductively active adults were used for a 21-day diuron and 3,4-DCA fish short-term reproductive assay (FSTRA). All the bioassays were conducted in a semi-static method. The LC50 of diuron and 3,4-DCA for embryo were; 632.5 mg/L (95% CI = 622.6 645, R2 = 0.98, 10 days) and 32.87 mg/L (95% CI = 27.90 - 38.74, R2 = 0.95, 96-hours), respectively. No behavioural toxicity symptoms were observed in both diuron and 3,4- DCA exposed individuals. The curve fit models (concentration-mortality) indicate a low concentration-dependent increase in the mortality rate for diuron and 3,4-DCA exposed adults. The LC50 trend was; larvae > juveniles > adults for both diuron and 3,4-DCA. Adult Javanese medaka was less susceptible to a slight increase in the concentration of diuron and 3,4-DCA. The fecundity of Javanese medaka exposed to diuron and 3,4-DCA were significantly affected (p < 0.05). Vitellogenin (VTG) concentration of diuronexposed females was significantly higher (p < 0.05) with 58.62 ± 0.29 ng/L and 55.64 ± 7.60 ng/L at 0.5 mg/L and 1.0 mg/L, respectively, but there was no significant difference (p > 0.05) in male fish at the concentrations tested. Non-monotonic dose-response (NMDR) in the gonadal tissues was observed. Abnormal gametogenesis was less prominent in exposed-male Javanese medaka but more obvious in the female Javanese medaka exposed to both diuron and 3,4-DCA. The 20-days exposed embryos to both diuron and 3,4-DCA showed significant difference (p < 0.05) NMDR physiological and morphological features. The acute toxicity on the different life stages indicated that diuron was less potent than 3,4-DCA. Conversely, the chronic exposure showed that diuron exerted more toxicity effects to Javanese medaka compared to 3,4-DCA. The disruption of fecundity and alteration in gonads histology implied reproductive toxicity of diuron and 3,4-DCA on Javanese medaka. The NMDR indicates a disruption in normal hormonal activity during embryonic development. The increase in VTG implied an oestrogenic effect on female Javanese medaka but no effect on male Javanese medaka at a concentration up to 1.0 mg/L. The non-linear/NMDR in embryonic development signified disruption of endocrine activity by diuron and 3,4-DCA. Generally, the age of Javanese medaka plays a vital role in its susceptibility to diuron and 3,4-DCA. Both diuron and 3,4-DCA disrupt the hormonal activities during reproduction and embryonic development of Javanese medaka. Therefore, they are potential endocrine-disrupting chemicals (EDCs). This finding strengthens the potential endocrine-disrupting effect of diuron and 3,4-DCA on non-target aquatic organisms. The response of Javanese medaka to diuron and 3,-4-DCA can predict the potential developmental and reproductive effects on other exposed aquatic vertebrates. Further research on multi-generation and ecotoxicogenomics to support these results would add information to existing data on the effect of diuron and 3,4-DCA on the survival, growth, and reproduction of Javanese medaka.